2021
DOI: 10.1002/pro.4246
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a pathogenic mutant of human protein tyrosine phosphatase PTPN2 (Cys216Gly) that causes very early onset autoimmune enteropathy

Abstract: PTPN2 is an important protein tyrosine phosphatase (PTP) that plays a key role in cell signaling. Deletions or inactivating mutations of PTPN2 have been described in different pathologies and underline its critical role in hematopoiesis, autoimmunity, and inflammation. Surprisingly, despite the major pathophysiological implications of PTPN2, the structural analysis of this PTP and notably of its pathogenic mutants remains poorly documented. Contrary to other human PTP enzymes, to date, only one structure of PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Compared to WT PTP1B, the intrinsic protein tyrosine phosphatase activity of the three mutants was found to be extremely low; the V184D mutant displayed around 5% residual activity, and the R221G and G259V mutants were almost inactive (Figure 2A). To assess the intrinsic protein tyrosine phosphatase activity of WT PTP1B and the three mutants, we carried out reverse-phase ultra-fast liquid chromatography (RP-UFLC) using a known tyrosine-phosphorylated peptide substrate of PTP1B (sequence: KGTGYphos-phoIKTE) derived from human STAT1 as previously described [28,29]. Compared to WT PTP1B, the intrinsic protein tyrosine phosphatase activity of the three mutants was found to be extremely low; the V184D mutant displayed around 5% residual activity, and the R221G and G259V mutants were almost inactive (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to WT PTP1B, the intrinsic protein tyrosine phosphatase activity of the three mutants was found to be extremely low; the V184D mutant displayed around 5% residual activity, and the R221G and G259V mutants were almost inactive (Figure 2A). To assess the intrinsic protein tyrosine phosphatase activity of WT PTP1B and the three mutants, we carried out reverse-phase ultra-fast liquid chromatography (RP-UFLC) using a known tyrosine-phosphorylated peptide substrate of PTP1B (sequence: KGTGYphos-phoIKTE) derived from human STAT1 as previously described [28,29]. Compared to WT PTP1B, the intrinsic protein tyrosine phosphatase activity of the three mutants was found to be extremely low; the V184D mutant displayed around 5% residual activity, and the R221G and G259V mutants were almost inactive (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The two other PTP1B mutants, R221G and G259V identified in PBMCL, were not analyzed in the Gunawardana et al study [7]. To further characterize the V184D, R221G, and G259V PTP1B mutants, transfection studies were carried out in HEK293T cells followed by immunoprecipitation and measurement of their intrinsic tyrosine phosphatase activity by RP-UFLC as previously described [29]. In agreement with the results reported above with the recombinant purified proteins, we found that the R221G and G259V mutants displayed no intrinsic protein tyrosine phosphatase activity while the V184D mutant displayed around 5% of the WT activity (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using HOPE (Venselaar et al, 2010) one can predict that the substitution takes place at the surface of the phosphatase domain but whether this impacts on the enzyme's interaction possibilities including substrate specificity, remains to be established. The situation is much more clear for the recently identified p.C216G variant (Parlato et al, 2020) because the amino acid change here involves the essential catalytic site cysteine (Nian et al, 2022). This renders the mutant protein enzymatically dead and consequently potentially substrate-trapping because catalysis is blocked but substrate affinity is maintained (Blanchetot et al, 2005).…”
Section: Documented Genetic Variability 21 Methodologymentioning
confidence: 99%
“…The current common strategy for targeting PTPN2 and PTP1B is substrate mimicking: structures similar to phosphorylated tyrosine, such as the difluoromethyl phosphate group, isothialidinone, and thiadiazolidinone dioxide motifs, which could interact with the catalysis site (P-loop and WPD loop), were widely used in the inhibitor design. In 2001, Zhang and co-workers identified a PTP inhibitor with a difluoromethyl phosphate scaffold (compound 1 , Figure ) through combinatorial library screening; its K i value for PTPN2 is 26 nM . In March 2023, they reported another potent difluoromethyl phosphate-based PTP1B/PTPN2 dual inhibitor DI-03 (compound 2 , Figure ) with improved potency (PTPN2/PTP1B IC 50 = 7.1:4.7 nM) .…”
Section: Introductionmentioning
confidence: 99%